2013
DOI: 10.1186/1476-511x-12-159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blood triglycerides on cardiovascular and all-cause mortality: a systematic review and meta-analysis of 61 prospective studies

Abstract: The relationship of triglycerides (TG) to the risk of death remains uncertain. The aim of this study was to determine the associations between blood triglyceride levels and cardiovascular diseases (CVDs) mortality and all-cause mortality. Four databases were searched without language restriction for relevant studies: PubMed, ScienceDirect, EMBASE, and Google Scholar. All prospective cohort studies reporting an association between TG and CVDs or all-cause mortality published before July 2013 were included. Risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
101
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(117 citation statements)
references
References 36 publications
10
101
4
2
Order By: Relevance
“…Recently, we showed that 1 SD increment in log-transformed TGs was accompanied with 19% lower risk of non-CVD mortality [67]. A contention in contrast with previous studies, which highlighted the linear relation between hypertriglyceridemia and mortality [68, 69]; one explanation would be that low TG could be a marker of malnutrition and weight loss which, in turn, may increase mortality risk in the population [70]. In our study, after CVD, cancer was the most common cause of death and it has been shown that the low TG and weight loss are poor prognostic signs in cancerous patients and are associated with poor survival [48–50, 71].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, we showed that 1 SD increment in log-transformed TGs was accompanied with 19% lower risk of non-CVD mortality [67]. A contention in contrast with previous studies, which highlighted the linear relation between hypertriglyceridemia and mortality [68, 69]; one explanation would be that low TG could be a marker of malnutrition and weight loss which, in turn, may increase mortality risk in the population [70]. In our study, after CVD, cancer was the most common cause of death and it has been shown that the low TG and weight loss are poor prognostic signs in cancerous patients and are associated with poor survival [48–50, 71].…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, triacylglycerol have been associated to 13% and 12% more odds of cardiovascular diseases and all-cause mortality, respectively (Liu et al, 2013). In addition, cardiovascular disease has a significant public health cost (Azambuja et al, 2008; de Oliveira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At present, hypertriglyceridemia has become more generally accepted as a risk factor for cardiovascular diseases (CVDs) (Ninomiya et al 2004;Miller et al 2011). A meta-analysis has shown that per 1 mmol/L TG increment increases the risks of CVDs and all-cause deaths by 13% and 12%, respectively (Liu et al 2013). Therefore, controlling TG may help to prevent CVDs and other causes of death.…”
Section: Introductionmentioning
confidence: 99%